2009
DOI: 10.1186/1472-6750-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and processing of a recombinant protein designed as a cleavable fusion to the endogenous Rubisco LSU protein in Chlamydomonas chloroplast

Abstract: BackgroundExpression of recombinant proteins in green algal chloroplast holds substantial promise as a platform for the production of human therapeutic proteins. A number of proteins have been expressed in the chloroplast of Chlamydomonas reinhardtii, including complex mammalian proteins, but many of these proteins accumulate to significantly lower levels than do endogenous chloroplast proteins. We examined if recombinant protein accumulation could be enhanced by genetically fusing the recombinant reporter pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…, 2004; Butt et al. , 2005) and plant and algal chloroplasts (Streatfield, 2007; Muto et al. , 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2004; Butt et al. , 2005) and plant and algal chloroplasts (Streatfield, 2007; Muto et al. , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…These include reporter proteins (Franklin et al. , 2002; Mayfield and Schultz, 2004; Muto et al. , 2009), a large complex mammalian single‐chain antibody (Mayfield et al.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the successful use of the microalga Chlamydomonas reinhardtii for production of therapeutic proteins , Muto et al, 2009, Rosales-Mendoza et al, 2012, Tran et al, 2009, Mayfield, 2013. Of particular interest are synthetic fusion proteins that combine the characteristics from different molecules to provide an enhanced physiological response (Mayfield, 2013).…”
Section: Cultivation Of Microalgae Currently Occurs In Either Open Ormentioning
confidence: 99%
“…Alternatively, transgenic algae can be used as bioreactors for the production of pharmaceuticals (Hawkins & Nakamura, 1999;Geng et al, 2003;Mayfield et al, 2003;Sun et al, 2003). For example, C. reinhardtii chloroplasts have been established as factories for the production of recombinant proteins Mayfield et al, 2007;Muto et al, 2009;Rasala et al, 2010) and offer efficient systems for high yield production of complex proteins which were properly folded into functional molecules such as recombinant antibodies Tran et al, 2009) and vaccines (Surzycki et al, 2009). Moreover, the development of efficient target genome editing methods to specifically knock down or knock out genes could be exploited for functional genomic analyses to enhance understanding of algal biology.…”
Section: Applications Of Random Mutagenesis and Targeted Gene Editingmentioning
confidence: 99%